Oncostatin M upregulates CD73 via the MAPK pathway in keratinocytes to promote an adenosine-dependent anti-inflammatory response in psoriasis - Giraulo, Caterina; De Palma, Giacomo; Plaitano, Paola; Esposito, Roberta; Morretta, Elva; Monti, Maria Chiara; Müller, Christa E.; Cicala, Carla; Morello, Silvana (Frontiers in Immunology, 2026)
IntroductionPsoriasis is a chronic inflammatory skin condition driven by activated epidermal keratinocytes, dermal fibroblasts, and immune cell infiltrates, which causes tissue injury. The ecto-5′-nucleotidase CD73/adenosine pathway plays a critical role in controlling inflammatory/immune responses, yet it is dysregulated in psoriasis patients. However, the expression and function of this pathway in psoriasis remain poorly explored.MethodsIn this study, we investigated the regulation of CD73 in keratinocytes and examined the anti-inflammatory effects of adenosine in keratinocytes and dermal fibroblasts under psoriatic-like conditions. HaCaT cells and primary normal human epidermal keratinocytes (NHEK) were stimulated with the M5 cytokine cocktail, comprising interleukin (IL)-1α, IL-17A, IL-22, oncostatin M (OSM), and tumor necrosis factor (TNF)-α, to induce a proinflammatory phenotype.ResultsM5-treated keratinocytes release IL-1β, IL-6, and IL-8, as well as the antimicrobial peptide S100A9, and exhibit activation of the signal transducer and activator of transcription (STAT), nuclear factor-kappa B (NF-κB), mitogen-activated protein kinase (MAPK), and phosphoinositide 3-kinase/protein kinase B (PI3K/Akt) pathways. We demonstrated that CD73 is upregulated in inflamed keratinocytes, with OSM identified as a regulator of CD73 expression in a Janus kinase/MAPK-dependent manner. High CD73 expression in inflamed keratinocytes is associated with increased adenosine production. In M5-stimulated keratinocytes, adenosine A2A receptors (A2AR) expression is increased, whereas A2BR expression is decreased. Functional analyses revealed that an A2AR agonist, and to a lesser extent an A2BR agonist, reduced IL-8 levels in inflamed keratinocytes. Similarly, M5-treated dermal fibroblasts released IL-1β, IL-6, and IL-8, and exhibited activation of inflammatory signaling pathways. In inflamed dermal fibroblasts, both A2AR and A2BR were upregulated, and IL-8 release was mitigated by an A2AR agonist.DiscussionIn conclusion, these results provide new insights into the mechanisms by which the CD73/adenosine axis can be modulated in psoriatic conditions and may guide the development of effective strategies to mitigate inflammation.